A ginástica circense à luz da pedagogia histórico-crítica - Almeida, Jamildo Rios de (2019)
From the theoretical-methodological contributions of the historical and dialectical materialism and the historical-critical pedagogy we define as general objective of the research: elaborate the concept of circus gymnastics in the light of the historical-critical pedagogy, contributing to the formulation of the body culture that is expressed in the school contents of physical education. In the first chapter we present an analysis of the links and relationships, starting from the historicity of what we understand today as body culture and circus. The purpose was to understand how it was configured in the history of body practices what we call circus gymnastics, in order to reflect on how the specificities of this uniqueness of human culture were established. In the second chapter our intention was to understand the knowledge that supports physical education. Thus, it was necessary to go to the genesis of knowledge that inaugurates the school disciplinary model in physical education, the positivist gymnastics. After that, we point to body culture as an object of knowledge of physical education. Finally, we seek subsidies in the foundations of historical-critical pedagogy to think about the problematic of knowledge and the contents necessary for the humanization of the subjects. The third chapter intends to point elements for a reflection on the concepts of circus gymnastics and other terminologies used to designate this content in school. We theoretically point out some possibilities of thinking about educational activity through historical-critical didactic foundations. The study allowed the following formulation: circus gymnastics is a part of culture, ontologically linked to the work process and considered of non-material order, whose production and consummation occur simultaneously by those who produce and those who consume. Its specificity retroacts from the complexification of essential traits of the gymnastic objectivations of the different ways of balancing, jumping, rolling/spinning, rocking/balancing, climbing, which are expressed in the activities historically produced by circus culture.